The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1403503
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of breast tissue index from MR data using fuzzy clustering

Abstract: The study objective was to develop a segmentation technique to quantify breast tissue and total breast volume from magnetic resonance imaging (MRI) data to obtain a breast tissue index (BTI) related to breast density. Our goal is to quantify MR breast density to improve breast cancer risk assessment for certain high-risk populations for whom mammography is of limited usefulness due to high breast density. A semi-automatic 3D segmentation technique was implemented based on a fuzzy c-means technique (FCM) to seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 6 publications
1
104
0
Order By: Relevance
“…Klifa [15] et al present a segmentation technique based on fuzzy clustering to quantify breast density from MRI data. Oliver et al [16] suggest an approach based on gross segmentation and the extraction of texture features of pixels with similar tissue appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Klifa [15] et al present a segmentation technique based on fuzzy clustering to quantify breast density from MRI data. Oliver et al [16] suggest an approach based on gross segmentation and the extraction of texture features of pixels with similar tissue appearance.…”
Section: Introductionmentioning
confidence: 99%
“…5 Other methods that can measure quantitative breast density have been developed and evaluated; including volumetric measurements made based on 3D MRI. [6][7][8][9][10][11][12][13][14][15] However, so far there have not been published results demonstrating the association between MRIbased density parameters and cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…MRI has been used to calculate the water content of a human breast via slices or slabs and with segmentation of 3D images with tailored sequences [24][25][26][27][28][29][30]. It has been shown that percent MRI-density correlates strongly with mammographic PD; however, MRI, as also discussed above for DBT, has been shown to underestimate breast density compared with conventional mammography.…”
Section: Mri Techniquementioning
confidence: 99%